The Keratinocyte Transcriptome in Psoriasis: Pathways Related to Immune Responses, Cell Cycle and Keratinization - Lorenzo Pasquali; Ankit Srivastava; Florian Meisgen; Kunal Das Mahapatra; Ping Xia; Ning Xu Landén; Andor Pivarcsi; Enikö Sonkoly (Medical Journals Sweden, 2018)
Psoriasis is a common immune-mediated disease resulting from altered cross-talk between keratinocytes and immune cells. Previous transcriptomic studies have identified thousands of deregulated genes in psoriasis skin; however, the transcriptomic changes confined to the epidermal compartment remained poorly characterized. The aim of this study was to characterize the transcriptomic landscape of psoriatic keratinocytes, using sorted CD45neg epidermal cells. Genes with functions in innate immunity, type I interferon response, cell cycle and keratinization were enriched among deregulated genes in psoriatic keratinocytes. Gene set enrichment analysis indicated the dominance of interleukin (IL)-22/IL-17A signatures in the epidermal psoriasis-signature. A set of deregulated genes overlapped with psoriasis-associated genetic regions, suggesting that genetic variations affecting gene expression in keratinocytes contribute to susceptibility to psoriasis. Several psoriasis-susceptibility genes, which were previously believed to be expressed preferentially or exclusively in immune cells, were identified as having altered expression in psoriatic keratinocytes. These results highlight the role of keratinocytes in the pathogenesis of psoriasis, and indicate that both genetic factors and an inflammatory microenvironment contribute to epidermal alterations in psoriasis.